New results on the proximal point algorithm in non-positive curvature metric spaces. (3rd July 2017) - Khatibzadeh, Hadi; Mohebbi, Vahid; Ranjbar, Sajad
Abstract: The subject of this paper is the inexact proximal point algorithm of usual and Halpern type in non-positive curvature metric spaces. We study the convergence of the sequences given by the inexact proximal point algorithm with non-summable errors. We also prove the strong convergence of the Halpern proximal point algorithm to a minimum point of the convex function. The results extend several results in Hilbert spaces, Hadamard manifolds and non-positive curvature metric spaces.